PENERAPAN PROGRAM LINIER UNTUK MINIMASI BIAYA PRODUKSI MENGGUNAKAN METODE GRAFIK(Studi Kasus: Pada Pabrik Karya Utama) - Arief Dwi Ramadhan; Heru Sutejo; Zaskia Aline Syahfitri; Jibril Olivia Arera; Enjel Bella Janet Maruapey; Yohosua Daniel Werimon (CV. ADIBA AISHA AMIRA, 2026)
This study aims to optimize the daily production costs at Karya Utama Factory, a medium-scale soybean processing industry. The main problem faced is determining the most economical production combination of tofu and tempeh amidst operational constraints, specifically the minimum daily requirement of 350 kg soybean absorption from the distributor. This applied quantitative research utilizes a two-variable Linear Programming model solved by the Graphical Method. The objective function is formulated to minimize daily production costs, bounded by raw material availability and market quota targets. The results within the feasible region prove that the optimal solution is achieved when the factory constantly produces 1,540 units of tofu and 600 units of tempeh daily. Implementing this combination yields the minimum total expenditure of Rp5,828,000 per day. Furthermore, the analysis uncovers the